ARG2, MAP4K5 and TSTA3 as Diagnostic Markers of Steroid-Induced Osteonecrosis of the Femoral Head and Their Correlation With Immune Infiltration - Yu, Rongguo; Zhang, Jiayu; Zhuo, Youguang; Hong, Xu; Ye, Jie; Tang, Susu; Liu, Nannan; Zhang, Yiyuan (Frontiers in Genetics, 2021)
Abstract Background: The diagnosis for steroid-induced osteonecrosis of the femoral head (SONFH) is hard to achieve under the early stage, which resulted in ineffective treatment options and a poor prognosis for most cases. The present study aimed at finding potential diagnostic markers of SONFH and analyzing the effect exerted by infiltration of immune cells in this pathology. Material/Methods: R software was adopted for identifying differentially expressed genes (DEGs) and conducting functional investigation based on the microarray dataset. Then we combined SVM-RFE, WGCNA, LASSO logistic regression and random forests (RF) algorithms for screening the diagnostic markers of SONFH and further verify by qRT-PCR. The diagnostic values were assessed through receiver operating characteristic (ROC) curves. Lastly, CIBERSORT was adopted for assessing the infiltration of immune cells and the relationship of infiltration-related immune cells and diagnostic markers. Results: We identified overall 383 DEGs here. This study found ARG2, MAP4K5 and TSTA3 (AUC = 0.980) to be diagnostic markers of SONFH. The results of qRT-PCR showed a statistically significant difference in all markers. Analysis of infiltration of immune cells indicated that neutrophils, activated dendritic cells and memory B cells were likely to show the relationship with SONFH occurrence and progress. Additionally, all diagnostic markers was different degrees of correlation with resting NK cells, T cells follicular helper, neutrophils, memory B cells and activated dendritic cells. Conclusions: In conclusion, ARG2, MAP4K5 and TSTA3 were considered as potential diagnostic genes for SONFH, and infiltration of immune cells may critically impact SONFH occurrence and progression.